(untitled) (Research, Society and Development, 2025)
The growth of technological innovations in the food sector has driven the expansion of plant-based products, motivated by changes in consumer behavior, environmental concerns, and demands for nutritionally adequate alternatives. This article aims to review and discuss the main technologies applied to the development of plant-based food products, as well as to measure the impact of consuming these foods on the prevention of NCDs (Non-Communicable Diseases). The results show that methods such as ultrasound, fermentation, extrusion, and shearing have contributed to more stable, sustainable, and sensorially attractive formulations, in addition to favoring the use of national raw materials and agro-industrial waste. Furthermore, the results also indicate that plant-based dietary patterns offer significant metabolic benefits, including reduced cholesterol, improved blood glucose levels, lower risk of obesity, and cardiovascular protection, due to the high fiber and bioactive compound content and the absence of cholesterol and saturated fats. Although the results are promising, the need for primary and longitudinal research to deepen the understanding of the effects of these diets and emerging technologies on population health is highlighted. It is concluded that technological advancement combined with the adoption of plant-based dietary patterns constitutes a relevant strategy for promoting public health and developing more sustainable and inclusive food systems.